Assistive technology and affective mediation - Garay, Nestor; Cearreta, Idoia; López, Juan; Fajardo, Inmaculada (Human Technology, 2006)
The lack of attention towards affective communication in assistive technology and disability research can be potentially overcome thanks to the development of affective computing and affective mediation areas. This document describes the main impairments and disorders that may involve affective communication deficits. We also present several affective mediation technologies that are being applied or may be integrated in assistive technologies in order to improve affective communication for a range of disabilities. Finally, we describe our experience with Gestele, an application that incorporates multimodal elements of affective mediation for people with mobility impairments, as well as the results of an empirical study conducted to evaluate the application's validity in communication via telephone.